2022
DOI: 10.4317/medoral.24944
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of vitamin C supplementation on bone healing: A systematic review

Abstract: Background The aim of the present systematic review was to evaluate the clinical effect of vitamin C on bone healing after bone fracture or bone reconstruction procedures. Material and Methods In October 2020, Cochrane Library, Scopus and PubMed-Medline databases were searched without restrictions to identify animal and human studies that fulfilled the eligibility criteria. Outcome measures were bone healing time, bone gain (mm), bone density and adverse events. The ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
7
0
3
Order By: Relevance
“…Vitamin C has a favourable impact on the spatio-temporal expression of transcripts associated with early resolution of in ammation and tissue remodelling. In addition, Barrios-Garay et al [34] have also shown from in vivo animal studies that vitamin C appears to accelerate bone formation due to increased osteoblastic proliferation and differentiation and its antioxidant function when pro-oxidant substances are added. These studies corroborate with the results obtained from the survey on the therapeutic uses of cowpea seeds.…”
Section: Therapeutic Uses Of Cowpeamentioning
confidence: 99%
“…Vitamin C has a favourable impact on the spatio-temporal expression of transcripts associated with early resolution of in ammation and tissue remodelling. In addition, Barrios-Garay et al [34] have also shown from in vivo animal studies that vitamin C appears to accelerate bone formation due to increased osteoblastic proliferation and differentiation and its antioxidant function when pro-oxidant substances are added. These studies corroborate with the results obtained from the survey on the therapeutic uses of cowpea seeds.…”
Section: Therapeutic Uses Of Cowpeamentioning
confidence: 99%
“…The skeletal matrix comprises an integrated framework of type 1 collagen, which serves as scaffolding for the mineral hydroxyapatite component of bone. Vitamin C is involved in collagen synthesis and modification of bone turnover through the wnt/β-catenin signaling pathway [ 31 , 32 ]. Although vitamin C deficiency is uncommon in the general population, several recent clinical case reports discuss the development of scurvy in patients with ARFID and its subsequent effects on bone health [ 30 , 33 ].…”
Section: Mediators Of Bone Deficits In Arfidmentioning
confidence: 99%
“…Однократное внутримышечное введение 0,5 мг/кг аскорбиновой кислоты при расширении верхней челюсти крыс через 24 ч после травмы стимулирует ее оссификацию [39] и ускоряет заживление экспериментального перелома большеберцовой кости крыс [5].…”
Section: антигипоксическая антиоксидантная и противовоспалительная ак...unclassified
“…Однако аналогичное введение равных объемов официнальных 5%-ных растворов АК и глюкозы либо 5%-ного раствора АК в том же периоде индуцирует формирование фиброзного сращения сопоставленных отломков вертлужной впадины [41,42]. Очаговое введение раствора аскорбиновой кислоты (0,5 мг/кг) непосредственно в область нарушенного соединения верхнечелюстных костей крыс через 24 ч после травмы также предотвращает ее оссификацию [5].…”
Section: антигипоксическая антиоксидантная и противовоспалительная ак...unclassified